ASSESSMENT OF CARPAL TUNNEL SYNDROME WITH ULTRASONOGRAPHY - Ahmed, Aliya; Malik, Ghazala; Imtiaz, Hassan; Riaz, Ramish; Badshah, Mazhar; Zameer, Shahla (Journal of Ayub Medical College Abbottabad, 2022)
Background: Carpal tunnel syndrome (CTS) is the most common nerve entrapment neuropathy caused by compression of median nerve at wrist as it passes through osseofibrous canal known as carpal tunnel. Epidemiological statistics shows one in every ten people develops the disease at any stage of life. CTS mostly affect females than males with mean age of 50. Clinical features are considered to be enough for establishing the diagnosis of carpal tunnel syndrome. However, nerve conduction studies give quantitative information regarding median nerve function therefore good at predicting outcome of intervention. Ultrasound being easily available, cost effective and real time is a promising modality for diagnosis and grading carpal tunnel syndrome. Methods: This correlational study was conducted in collaboration of Neurology and Radiology Department of Pakistan Institute of Medical Sciences, Islamabad from January 2018 to January 2019. Total 50 patients with 85 wrists involved were included in the study. All patients with positive nerve conduction study were included. Patient with history of wrist trauma were not included. Detailed history and clinical features were recorded. All patients with positive result on nerve conduction studies underwent ultrasound examinations. Fifty control wrists were also included to establish the normal median nerve cross sectional area value in our study population. Results were recorded. Data was analyzed and appropriate statistical tests were applied by using SPSS v20. Results: Mean cross sectional area of median nerve for controls was 6.34±1.23. Mean cross sectional area of median nerve for mild CTS was 8.05±1.72, moderate CTS was 11.15±2.32, severe was 17.49±4.93. Strong correlation was found between (r=0.76, p-value <0.0001) between increased cross-sectional area on Ultrasonography and severity of CTS on NCS. Other finding on Ultrasonography included flattening in 4 and fluid in 10 affected wrists. Conclusion: Increased cross-sectional area on Ultrasonography and severity of carpal tunnel syndrome on nerve conduction studies are very strongly correlated.